Effect of Formulation Factors on Transcorneal Permeation of Acetazolamide from Aqueous Drops: In vitro andIn vivo Study - Manchanda, Satish (Asian Journal of Pharmaceutics (AJP), 2016)
Aim: The purpose of this research was to evaluate the effect the formulation factors on in vitro permeation of acetazolamide (ACZ) through freshly isolated goat corneas. Materials and Methods: Different formulation factors were studied. The concentration of drug was raised from 0.025% to 0.1% (w/v) and pH was also varied within the range of 6-8. Several viscosity modifiers and preservatives were also added to study their effect on permeation. Finally, the formulation with the optimized factors was used to study ocular hypotensive activity of the drug in rabbits. Results and Discussion: Raising concentration of the drops from 0.025% to 0.1% (w/v) significantly (P < 0.05), increased drug permeation, but decreased the percent permeation. An increase in the pH of the drops from 6.0 to 8.0 resulted in significant (P < 0.05) change in drug permeation. Eye drops containing benzalkonium chloride (BKC) showed significantly (P < 0.05) higher permeation as compared with control formulation. Compared with control formulation, ACZ 0.1% (w/v) drop containing viscosity modifier produced significant (P < 0.05) decrease in permeation. A formulation having BKC showed increased hypotensive activity as compared to the control formulation. Conclusion: The study reflects that the permeation of ACZ is greatly influenced by formulation factors and permeation was found to be concentration and pH dependent.